Sex/gender perspectives in language and literature textbooks published by Santillana. The case of “Todos protagonistas” (Anclajes, 2022)
This study stems from a doctoral thesis entitled “Gender and Literature in Textbooks for Argentine Secondary Schools (1984-2011)” sponsored by CONICET and directed by José Maristany and co-directed by Analía Gerbaudo. The study’s main objective was to reconstruct the way in which discussions on gender during certain pivotal moments in history impacted language and literature textbooks published for Argentine secondary schools. To this end, a book from the series “Todos protagonistas”, published during 2004 and 2006, is examined. Document analysis, historical review, and semi-structured interviews are used to explore the impact of the State and of educational publishers on sex/gender perspectives that appeared in these books.
Keywords: Textbook; Language; Literature; Gender